Studies on the Coagulation of the Blood in Patients Treated with Extra-Corporeal Circulation - de Vries, S. I; van Creveld, S; Groen, P; Müller, E; Wettermark, M (Thrombosis and Haemostasis, 1961)
An extensive investigation of the coagulation mechanism was performed in 21 patients suffering from a congenital heart failure and exposed to surgical treatment with the aid of extra-corporeal circulation. The results have been discussed and suggestions given for the preoperative and postoperative mode of investigation in future. Only three factors may be considered a possible contraindication for the operation, namely1. a persistent and marked thrombocytopenia,2. fibrinogenopenia and3. a high degree of fibrinolysis.Before a final decision to operate is taken an attempt should be made to restore the impaired coagulation mechanism. The necessity of a preoperative analysis and a close cooperation between the surgeon and the coagulationist before, during and after the operation have been stressed.